2020
DOI: 10.1002/app.49087
|View full text |Cite
|
Sign up to set email alerts
|

Optimization of printing parameters for improvement of mechanical and thermal performances of 3D printed poly(ether ether ketone) parts

Abstract: Many processing parameters can be adjusted to optimize the fused filament fabrication (FFF) process, a popular and widely used additive manufacturing techniques for plastic materials. Among those easily adjusted parameters are the nozzle temperature, printing speed, raster orientation, and layer thicknesses. Using poly(ether ether ketone) (PEEK) as the base material, a design of experiments analysis was performed on the main FFF parameters. A response surface methodology was applied to analyze the results and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
94
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 101 publications
(112 citation statements)
references
References 39 publications
3
94
0
Order By: Relevance
“…Numerous parameters can be adjusted to modify the mechanical properties of the product, including shell number, layer thickness, infill percentage, deposition angle, build orientation, raster width, displacement speed of printing head, and temperature of liquefier 9 . Those parameters modify the structure of the built parts, namely porosity and crystallinity, 10 and thus the mechanical properties 11 . Printing parameters may influence the thermal cycles and cause a differential of shrinkage, which could cause distortion, internal residual stress, and lower mechanical properties 12 .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Numerous parameters can be adjusted to modify the mechanical properties of the product, including shell number, layer thickness, infill percentage, deposition angle, build orientation, raster width, displacement speed of printing head, and temperature of liquefier 9 . Those parameters modify the structure of the built parts, namely porosity and crystallinity, 10 and thus the mechanical properties 11 . Printing parameters may influence the thermal cycles and cause a differential of shrinkage, which could cause distortion, internal residual stress, and lower mechanical properties 12 .…”
Section: Introductionmentioning
confidence: 99%
“…The poor filament adhesion would increase the anisotropy of the printed part by lowering the mechanical properties in the building direction 21 . Other phenomena might also influence the effect of temperature on mechanical properties, such as crystallinity 10,22 or matrix degradation, 23 and cause a more difficult understanding of this thermal behavior. Printing speed and temperature are thought to interact, since printing speed can modify the time between two adjacent depositions, which is the time allowed for a filament to weld before the temperature falls below the glass transition 24 .…”
Section: Introductionmentioning
confidence: 99%
“…This latter transition is created by the organization of molecular chains in the crystalline PPS lamellae due to increased mobility during heating. [ 27,46 ] As shown in Figure S1, PPS is a semicrystalline material as confirmed by the first heating and by its degree of crystallinity (see Table 4). From these results, it can be concluded that PPS kept its semicrystalline property after the cooling state of the printing process.…”
Section: Resultsmentioning
confidence: 66%
“…On the contrary, high layer thickness interrupts the adhesion between adjacent layers. [ 52 ] According to El Magri et al [ 27 ] , printing parts with a thin layer thickness caused a higher cohesion among layers and an increase in surface contact between printed PEEK's infill lines. Thus, the generation of strong interlayer bonding zone is observed.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation